Moderating Technology, Stress, and Performance in Hospitality - Lestari, Nurul Sukma; Dinitri, Seruni; Pratiwi, Pratiwi; Yulianty, Jessyca; Rojali, Muhammad (Stupa, 2025)
This study investigates how technology adoption, job stress, and the role of supervisors in the hospitality industry influence performance and the supervisor's role as a moderator. This study looks at these dynamics to provide insight into strategic management techniques that increase productivity, increase worker happiness, and drive long-term sustainability in the highly competitive hospitality industry. This quantitative research uses descriptive methods and uses SEM-PLS to test the data. The population is all employees of local 5-star hotels in Jakarta that have been operating for 20 years, with 400 respondents. The data collection technique uses non-probability sampling with purposive sampling. The findings of this research show that adopting technology improves performance but also increases work stress. Managed stress can boost performance. The supervisor's role amplifies the impact of technology and helps manage stress, contributing directly to improved performance. The research findings have theoretical significance and relevance, especially for the hotel industry. The hospitality industry can use the research findings to develop more effective ways to improve job performance while considering the critical role of supervisors in overcoming difficulties in implementing new technologies, paying attention to employee mental health so that operations can run smoothly, and encouraging sustainable practices